KORELASI KEGIATAN MENTORING KE-ISLAMAN BERHUBUNGAN DENGAN PRESTASI AKADEMIK MK. AKHLAK, IBADAH DAN MUAMMALAH - Wahyu Riyaningrum, Ragil Setiyabudi, Tina Muzaenah, Itsna Nurrahma Mildaeni (Jurnal Ilmiah Keperawatan, 2022)
The coaching model that is considered effective is "assistance-monitoring" mentoring with peers, as has been implemented in schools or colleges and has been proven to be able to shape and cultivate an Islamic lifestyle for students. Students at the Universitas Muhammadiyah Purwokerto (UMP) who act as mentors in mentoring activities are their seniors, while those who are mentoring participants are their juniors called mentees.